Sosialisasi Pentingnya Berorganisasi dalam Pengembangan Karakter dan Keterampilan Berpikir Kritis Mahasiswa - Anggara Dwinata; Minto; Noer Af’idah; Muhammad Nuruddin; Emy Yunita Rahma Pratiwi; Sayid Marifatulloh; Hawwin Fitra Raharja; Claudya Zahrani Susilo; Eko Hardinanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
Organizations are a real means for students to develop aspects of character development and critical thinking skills. At Universitas Nusantara PGRI Kediri there are various organizations that are able to provide insight for students in developing their competencies. The aim of this Community Service activity is to provide insight into the importance of organizing for new students in developing character and critical thinking skills. The Community Service Method is socialization which includes preparation, implementation, documentation and evaluation stages. The essence of implementing socialization activities is sharing knowledge and brainstorming. The participants in the Community Service activities are all new students from the Elementary School Teacher Education Study Program for the 2022/2023 academic year. The positive results obtained from socialization activities have a positive impact on the importance of joining organizations for students as a form of implication in increasing scientific insight and networking, responsiveness in problem solving, improving communication and leadership skills, training entrepreneurial skills, administrative governance, forming a disciplined and responsible attitude. responsibility, independence, forming a high work ethic, and forming social attitudes.